以日本视角论述钓鱼群岛（尖阁诸岛）的主权归属 = The sovereignty of Diaoyu (Senkaku) Islands : the Japanese perspective - 刘志强 Liu, Zhiqiang (2011)
自从中国与日本于1969年开始爆发钓鱼群岛（尖阁诸岛）的主权争议以来，两国政府与学者都极力通过国际法来证明其领有权，而中方无论采取哪种国际法原理，其结论一定是“钓鱼岛是中国自古以来的固有领土”。但是，如果将现今钓鱼岛受日本所统治的事实与中方的说法进行对比，就能看出其中的矛盾所在：既然钓鱼岛是中国“自古以来的固有领土”，那为什么现今钓鱼岛是被日本所统治？日本又是通过什么国际法原理来取得钓鱼岛的统治权？对此，本文将通过国际法来分析日本领有钓鱼岛的主权依据，并解释为什么钓鱼岛的主权是属于日本，而非中国所有。1969 marks the beginning of the Diaoyu (Senkaku) islands’ dispute between China and Japan. Government officials and scholars from both countries have tried to lay claims to the islands using International Law. Regardless of the different International Law applied to this issue, China maintains that “Diaoyu islands have been a part of the Chinese territory since ancient times”. However this seems to contradict the present situation as one can observe that Diaoyu Islands are under the Japanese effective control. Why are the Japanese laying claims to the Diaoyu Islands when the islands have been a part of the Chinese territory since ancient times? What principles of the International Law are the Japanese using to justify their sovereignty over the Diaoyu Islands? This paper analyzes the Japanese’ claims to the Diaoyu Islands using the principles of International Law and attempts to justify the sovereignty of Diaoyu Islands from the Japanese perspective